2018
DOI: 10.1186/s12934-018-0948-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fate of pregnene-based steroids in the lactonization pathway of multifunctional strain Penicillium lanosocoeruleum

Abstract: BackgroundMetabolic activities of microorganisms to modify the chemical structures of organic compounds became an effective tool for the production of high-valued steroidal drugs or their precursors. Currently research efforts in production of steroids of pharmaceutical interest are focused on either optimization of existing processes or identification of novel potentially useful bioconversions. Previous studies demonstrated that P. lanosocoeruleum KCH 3012 metabolizes androstanes to the corresponding lactones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The performance of BVMOs of the Penicillium vinaceum AM110 strain is comparable to other species of the genus Penicillium . For example, P. lanosocoeruleum converts progesterone to testololactone in 88% yield in 72 h (the value very similar to the current study), but pregnenolone is converted into a mixture of products, with only 44% yield of testololactone in 72 h [ 36 ] (in the current study on P. vinaceum , testololactone is the sole detected product with 91% yield after 48 h). P. lanosocoeruleum converts DHEA ( 1 ) solely to testololactone with 96% yield in 24 h [ 35 ], which is a different route, including isomerization, than in the current study, where only BVO is observed.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The performance of BVMOs of the Penicillium vinaceum AM110 strain is comparable to other species of the genus Penicillium . For example, P. lanosocoeruleum converts progesterone to testololactone in 88% yield in 72 h (the value very similar to the current study), but pregnenolone is converted into a mixture of products, with only 44% yield of testololactone in 72 h [ 36 ] (in the current study on P. vinaceum , testololactone is the sole detected product with 91% yield after 48 h). P. lanosocoeruleum converts DHEA ( 1 ) solely to testololactone with 96% yield in 24 h [ 35 ], which is a different route, including isomerization, than in the current study, where only BVO is observed.…”
Section: Resultssupporting
confidence: 73%
“…Our earlier studies with biotransformations of steroids by the fungi of genus Penicillium [ 31 , 32 , 35 , 36 ] have revealed large diversity of metabolic fates of the substrates. Baeyer-Villiger oxidation, isomerizations, and hydroxylations with diverse product stereochemistry were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them exhibited similar or higher inhibiting activity towards steroidal 5α‐reductase and low affinity to the androgen receptor as compared to finasteride (Garrido et al ., 2011). The ability to oxidize ketosteroids to lactones was detected in fungi of different taxonomic classes, especially Apergillu s, Fusarium and Penicillium (Świzdor et al ., 2012; Świzdor et al ., 2018; Panek et al ., 2020a). The formation of hydroxylactones from C 19 steroids was demonstrated for Beauveria bassiana (Świzdor et al ., 2011; Świzdor et al ., 2014) and Isaria fumosorosea (previously classified as Spicaria fumosorosea ) (Lobastova et al ., 2015; Kozłowska et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxylation occurs mainly at the 6β and/or 11α positions [1,4,5,24,[29][30][31][32][33][34][35][36][37], but hydroxylation at the 14α [29,31,[33][34][35][36]38,39], 7α [33][34][35]38,39], 7β [34], 11β [30,38], 17α [24,30,32], 9α [31], 8β [31], 16α [32], 15α [32,33,40], 15β [33,34], 21 [1,36] and 12β [24,25] positions is also possible in the fungal cultures. The Baeyer-Villiger oxidation of progesterone is possible for biotransformation by some Aspergillus or Penicillium species [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%